Evaluating SIKS-NG's Performance in Jabon District Social Welfare - Mursyidah, Lailul; Nofi, Nofi (Indonesian Journal of Cultural and Community Development, 2024)
Background: The integration of information systems into social welfare initiatives is increasingly important in rural areas. Specific Background: This study examines the effectiveness of the Next-Generation Social Welfare Information System (SIKS-NG) in a specific village, highlighting the role of human resources and supporting infrastructure. Knowledge Gap: Previous research emphasizes the need for trained personnel but lacks comprehensive analysis of resource adequacy. Aims: The research assesses the effectiveness of SIKS-NG in updating social assistance data, focusing on operators and available resources. Results: Findings reveal that effective implementation relies on competent operators and sufficient technological resources, such as computers and smartphones. Novelty: This study offers a comparative analysis with prior research, highlighting improved resource provision. Implications: The results emphasize the need for local governments to invest in human capital and technology to enhance social welfare outcomes and address poverty effectively. Highlights : Effective implementation of SIKS-NG relies on trained operators. Adequate technological resources, including computers and smartphones, are essential. Local government investment in human capital enhances social welfare outcomes. Keywords: Social Welfare, Information System, SIKS-NG, Rural Development, Human Resources